Սարգիս Կուկունյան - Գ. Ս. Խուդինյան (Հայկական ԽՍՀ գիտությունների ակադեմիա)
Когда в Западной Армении в 80-е годы XIX века началось гайдукское движение, восточноармянская молодежь горячо откликнулась на их призыв о помощи. Одним из первых решил отправиться в Западную Армению вольнослушатель Петербургского университета Саркис Кукунян. When the haiduk movement started in West Armenia in the 80's of the 19th century, young men of East Armenia warmly responded to the call of help. One of the first, Sarkis Kukunian, from the St. Petersburg university, decided to go to West Armenia.
Keywords: History; Biography; Political Science; Auxiliary Sciences of History; D History; J Political Science